PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 3-6 BULAN DI BIDAN PRAKTEK MANDIRI NURUL UMAIRA TITI PAPAN TAHUN 2019 - Niasty Lasmy Zaen; Ria Arianti (Jurnal Ilmiah Kebidanan Imelda, 2019)
Sleep is one form of baby's adaptation to the environment. Shortly after birth, babies usually sleep for 16-20 hours a day. Entering the age of 2 months the baby starts sleeping more nights than noon. Influence of infant massage on sleep quality in infants aged 3-6 months in the midwife independent practice nurul umaira in 2019, research methodology The method used in this study is Quasi Experimental Designs with nonequavalein control group types namely the experimental group and the control group in the study selected not random all mothers who have infants aged 3-6 months in the midwife independent practice nurul umaira in 2019 that is as many as 20 people whose data was taken in December 2019. Based on the Mann Withney statistical test as presented in table 4.5 obtained Z count value = 3.033 with p -value = 0.002, because of the p-value (0.002) <α (0.05), which means that there is an influence on the quality of sleep of infants aged 3-6 months who do baby massage with those who do not do baby massage. Where, the quality of sleep for infants aged 3-6 months who do baby massage is better than the quality of baby sleep that is not done baby massage. Thus it was concluded that there was a significant effect of infant massage on sleep quality of infants aged 3-6 months in the Midwife of Independent Practice Nurul Umaira in 2019.